2015
DOI: 10.1021/acs.jpcc.5b02849
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Oxygen Reduction Reaction on Platinum Alloys: A Computational and Experimental Study

Abstract: The development of Pt-based alloys for oxygen reduction reaction (ORR) is an important subject to enhance the performance of polymer electrolyte membrane fuel cells (PEMFCs) and metal–air batteries. Herein, ORR on Pt alloys with smaller and larger dopants in both Pt-shelled and cored alloys have been extensively investigated from both computational and experimental approaches to rationalize the detailed mechanism. Our density functional theory (DFT) based calculations found that Pt alloying with smaller dopant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…These adsorption energies can be tuned by alloying and thereby improve the catalytic activity compared to pure elements. [4][5][6][7][8][9] In this paper, we introduce a methodology for calculating adsorption energies on a class of complex alloys, namely high-entropy alloys (HEAs), which may be defined as near-equimolar alloys of five or more elements. [10][11][12] Such alloys were first discovered in 2004 but have drawn interest as catalytic materials only in the past couple of years.…”
Section: Introductionmentioning
confidence: 99%
“…These adsorption energies can be tuned by alloying and thereby improve the catalytic activity compared to pure elements. [4][5][6][7][8][9] In this paper, we introduce a methodology for calculating adsorption energies on a class of complex alloys, namely high-entropy alloys (HEAs), which may be defined as near-equimolar alloys of five or more elements. [10][11][12] Such alloys were first discovered in 2004 but have drawn interest as catalytic materials only in the past couple of years.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the ∆E O descriptor can be considered an extension and application of the d-band center model in electrocatalysis, as the adsorption/binding energy of oxygen has been shown to correlate with the d states of the surface atoms to which the atom/molecule binds [13,37]. Generally, an upward shift of the d-band center to Fermi level results in a stronger binding [13,17,24]. However, both the d-band center model and the oxygen-binding energy descriptor have limitations [14,50,51].…”
Section: Correlation Of the Orr Activity With The Oxygen Binding Enermentioning
confidence: 99%
“…However, both the d-band center model and the oxygen-binding energy descriptor have limitations [14,50,51]. For example, Lin et al reported that the ORR activity of the Pt-cored alloy (Pt@M, M = Co, Cu, Pd, and Au) catalysts does not correlate well with the d-band center of surface Pt [17]. Yu et al showed that the binding energies of O do not always correlate with those of OH [52].…”
Section: Correlation Of the Orr Activity With The Oxygen Binding Enermentioning
confidence: 99%
See 1 more Smart Citation
“…And based on previous descriptions, ensemble effects occur with the presence of hetero-atoms on shell surfaces, meaning ensemble effects are present in core-shell electrocatalysts with alloy shells. As for M@Pt core-shell-structured electrocatalysts, all M atoms are in the subsurface and have no direct contact with adspecies; therefore, the activity of Pt shells is mainly affected by stain and electronic effects [600]. System studies focused on ensemble effects in core-shell-structured electrocatalysts with alloy shells cannot be found in literature for the purpose of this review but similar studies on alloyed [601,602] or decorated [603] electrocatalysts have been carried out by several groups, with the possibility that these investigated ensemble effects in alloy electrocatalysts can be used to explain the ensemble effects in core-shell-structured electrocatalysts.…”
Section: Ensemble Effectmentioning
confidence: 99%